Los determinantes sociales y económicos de la salud. Asuntos teóricos y metodológicos implicados en el análisis (2014)
ABSTRACT: The studies on health determinants are questioned because they show differences on health results between social strata, without explaining the doctrinaire referents they are based on, or establishing the determination processes involved in the analysis. Likewise, it is brought into question how they frequently omit the relational character of the groups, sectors or social classes being analyzed. For this reason, the objective of this review was to contribute some elements that provide a basis for the knowledge field, both on the theoretical as well as on the practical aspect, which have a central role in any research on this topic regardless if they are explicit or not. We analyzed contributions from some social justice theories as well as eco-social epidemiology and studies on lifestyles coming from medical sociology. Likewise, we reviewed basic concepts on social stratification and socio-economic position that are repetitively used in this field of knowledge.